Competing Indentation Deformation Mechanisms in Glass Using Different Strengthening Methods - Luo, Jian; Lezzi, Peter J.; Vargheese, K. Deenamma; Tandia, Adama; Harris, Jason T.; Gross, Timothy M.; Mauro, John C. (Frontiers in Materials, 2016)
Chemical strengthening via ion exchange, thermal tempering, and lamination are proven techniques for strengthening of oxide glasses. For each of these techniques, the strengthening mechanism is conventionally ascribed to the linear superposition of the compressive stress profile on the glass surface. However, in this work we use molecular dynamics simulations to reveal the underlying indentation deformation mechanism beyond the simple linear superposition of compressive and indentation stresses. In particular, the plastic zone can be dramatically different from the commonly assumed hemispherical shape, which leads to a completely different stress field and resulting crack system. We show that the indentation-induced fracture is controlled by two competing mechanisms: the compressive stress itself and a potential reduction in free volume that can increase the driving force for crack formation. Chemical strengthening via ion exchange tends to escalate the competition between these two effects, while thermal tempering tends to reduce it. Lamination of glasses with differential thermal expansion falls in between. The crack system also depends on the indenter geometry and the loading stage, i.e., loading vs. after unloading. It is observed that combining thermal tempering or high free volume content with ion exchange or lamination can impart a relatively high compressive stress and reduce the driving force for crack formation. Therefore, such a combined approach might offer the best overall crack resistance for oxide glasses.